Acute mesenteric ischaemia in refractory shock on veno-arterial extracorporeal membrane oxygenation. Issue 1 (27th May 2020) - Renaudier, Marie; de Roux, Quentin; Bougouin, Wulfran; Boccara, Johanna; Dubost, Baptiste; Attias, Arié; Fiore, Antonio; de'Angelis, Nicola; Folliguet, Thierry; Mulé, Sébastien; Amiot, Aurélien; Langeron, Olivier; et al.
Abstract: Background: Acute mesenteric ischaemia is a severe complication in critically ill patients, but has never been evaluated in patients on veno-arterial extracorporeal membrane oxygenation (V-A ECMO). This study was designed to determine the prevalence of mesenteric ischaemia in patients supported by V-A ECMO and to evaluate its risk factors, as well as to appreciate therapeutic modalities and outcome. Methods: In a retrospective single centre study (January 2013 to January 2017), all consecutive adult patients who underwent V-A ECMO were included, with exclusion of those dying in the first 24 hours. Diagnosis of mesenteric ischaemia was performed using digestive endoscopy, computed tomography scan or first-line laparotomy. Results: One hundred and fifty V-A ECMOs were implanted (65 for post-cardiotomy shock, 85 for acute cardiogenic shock, including 39 patients after refractory cardiac arrest). Overall, median age was 58 (48–69) years and mortality 56%. Acute mesenteric ischaemia was suspected in 38 patients, with a delay of four (2–7) days after ECMO implantation, and confirmed in 14 patients, that is, a prevalence of 9%. Exploratory laparotomy was performed in six out of 14 patients, the others being too unstable to undergo surgery. All patients with mesenteric ischaemia died. Independent risk factors for developing mesenteric ischaemia were renal replacement therapy (odds ratio (OR) 4.5, 95% confidence interval (CI) 1.3–15.7, p =0.02) and onset of a second shock within the first five days (OR 7.8, 95% CI 1.5–41.3, p =0.02). Conversely, early initiation of enteral nutrition was negatively associated with mesenteric ischaemia (OR 0.15, 95% CI 0.03–0.69, p =0.02). Conclusions: Acute mesenteric ischaemia is a relatively frequent but dramatic complication among patients on V-A ECMO.